Association Between Psychological Distress, Cognitive Complaints, and Neuropsychological Status After a Severe COVID-19 Episode: A Cross-Sectional Study - Gouraud, Clément; Bottemanne, Hugo; Lahlou-Laforêt, Khadija; Blanchard, Anne; Günther, Sven; Batti, Salma El; Auclin, Edouard; Limosin, Frédéric; Hulot, Jean-Sébastien; Lebeaux, David; Lemogne, Cédric (Frontiers in Psychiatry, 2021)
Background Cognitive complaints are frequent after COVID-19 but their clinical determinants are poorly understood. This study aimed to explore the associations of objective cognitive performances and psychological distress with cognitive complaints in COVID-19 survivors. Materials and Methods Patients previously hospitalized for COVID-19 in a university hospital during the first wave of COVID-19 pandemic in France were followed-up at one month after their admission. Cognitive complaints were self-reported and standardized instruments were used to assess neuropsychological status (Digit Symbol Substitution Test, Semantic Verbal Fluency Test, Mini Mental Status Examination) and psychological distress (Hospital Anxiety and Depression Scale, HADS). Multivariable analyses were adjusted for age, sex, admission in intensive care unit (ICU) and C-reactive protein level. Results One hundred patients (34% women, median age: 60 years (interquartile range: 49-72)) completed the neuropsychological assessment at follow-up. In multivariable analyses, cognitive complaints at one-month were associated with greater HADS score (OR for one interquartile range: OR: 1.96, 95% CI: 1.08-3.57) and older age (OR: 1.05, 95% CI: 1.01-1.09) and, negatively, with admission in ICU (OR: 0.22, 95% CI: 0.05-0.90). In contrast, none of the objective neuropsychological test scores was significantly associated with cognitive complaints. Exploratory analysis showed that cognitive complaints were associated with both anxiety and depressive symptoms. Discussion These preliminary results suggest that cognitive complaints at one month after a hospitalization for COVID-19 are associated with psychological distress, independently of objective neuropsychological status. Anxiety and depression symptoms should be systematically screened in patients presenting with cognitive complaints after a severe COVID-19 episode.